[(11)C]PBR28 or [(18)F]PBR111 detect white matter inflammatory heterogeneity in multiple sclerosis - Datta,G; Colasanti,A; Kalk,N; Owen,DR; Scott,G; Rabiner,EI; Gunn,R; Lingford-Hughes,A; Malik,O; Ciccarelli,O; Nicholas,R; Nie,L; et al. (Journal of Nuclear Medicine, 2017)
Objective: To assess microglial activation in lesions and in normal appearing white matter of multiple sclerosis (MS) patients using positron emission tomography (PET). Methods: 34 MS patients (7 with secondary progressive MS (SPMS), 27 with relapsing remitting MS (RRMS)) and 30 healthy volunteers, genetically stratified for translocator protein (TSPO), binding status underwent PET scanning with TSPO radioligands ((11)C-PBR28 or (18)F-PBR111). Regional TSPO availability was measured as a distribution volume ratio (DVR) relative to the caudate (a pseudo-reference region). White matter lesions (WML) were classified as "active" (DVR highest in the lesion), "peripherally active" (peri-lesional DVR highest), "inactive" (DVR highest in surrounding normal appearing white matter, NAWM) or "undifferentiated" (similar DVR across lesion, peri-lesional and NAWM volumes). Results: The mean DVR in NAWM of patients was greater than that of the healthy volunteer white matter for both radioligands. Uptake for individual WML in patients was heterogeneous, but the median WML DVR and NAWM DVR for individual patients were strongly correlated (ρ = 0.94, P = 4x10-11). A higher proportion of lesions were inactive in patients with SPMS (35 %) than RRMS (23 %), but active lesions were found in all patients, including those on highly efficacious treatments. Conclusion: TSPO radioligand uptake was increased in brains of MS patients relative to healthy controls with two TSPO radiotracers. WML showed heterogeneous patterns of uptake. Active lesions were found in patients with both RRMS and SPMS. Their independent prognostic significance needs further investigation.